Nanoemulsion carriers for drug delivery: Assessment of environmental hazards. (1st July 2023) - Gomes, Susana I.L.; Guimarães, Bruno; Gasco, Paolo; Blosi, Magda; Costa, Anna L.; Scott-Fordsmand, Janeck J.; Amorim, Mónica J.B.
Abstract: Nanoemulsions (NEs) have been extensively studied as carriers for drug delivery, since these provide a good alternative to the existing non-nano systems, while promoting their target delivery and controlled release. NEs are considered safe drug carriers from a pre-clinical perspective, but there is currently no information on their ecotoxicological effects. In the present study we investigated the toxicity of a NE material (lecithin, sunflower oil, borate buffer) designed to be used as a liposomal excipient for eye drops, further referred to as (Lipid Particle:LP) LP_Eye and its dispersant (borate buffer) (LP_Eye disp.). Effects were assessed using two model species in soil ecotoxicology in LUFA 2.2 soil: Enchytraeus crypticus (Oligochaeta) and Folsomia candida (Collembola), based on the OECD standard guideline (28 days) and its extension, a longer-term exposure (56 days). The endpoints evaluated included survival, reproduction, and size. LP_Eye and LP_Eye disp. were toxic to E. crypticus and F. candida, affecting all measured endpoints. The toxicity of LP_Eye in E. crypticus seemed to be induced by the dispersant, whereas for F. candida, more sensitive, this was less explanatory. There were no indications that toxicity increased with longer exposure. Current results provide ecotoxicological data for a group of NMs that was absent, revealing toxicity to relevant environmental species. Indications were that the dispersant contributed to most of the observed effects, thus there is room to improve the formulation and achieve lower environmental impact. Graphical abstract: Graphical abstract. Image 1 Highlights: Nanoemulsions (NEs) ecotoxicity is virtually unknown. Hazardss of NE with medical application were assessed in E. crypticus and F. candida. NE was toxic to these soil invertebrates (survival, reproduction, size). The NE dispersant seems to explain most of the toxicity. The NE formulation could be improved to reduce environmental impacts.